Impact of climate variability and environmental policies on vegetation dynamics in the semi-arid Tigray - Amare Sisay Tefera; Zenebe Girmay Siyum; Daniel Hagos Berhe; Belay Manjur Gebru (Discover Environment, 2024)
Abstract Anthropogenic and climate-related phenomena are among the main factors responsible for variations in vegetation structure and composition worldwide. However, studies that integrate the effects of human activities and climate variability in fragile tropical ecosystems, including the semi-arid Tigray region, are lacking. The objective of this study was to examine the effects of climate variability and environmental policy changes on the spatial distribution and pattern of vegetation cover in the semi-arid Tigray region of Ethiopia over the past four decades. We used satellite-based vegetation index (normalized difference vegetation index) and monthly rainfall data to analyze the relationship between vegetation cover and climatic variability. Residual analysis was also used to further disentangle the effects of climatic variability and environmental policy on vegetation cover. The regression analysis (r2 = 0.19) showed an insignificant causal relationship between vegetation dynamics and precipitation over the 41-years study period. This study also highlighted negative impact of the global rise in temperature on vegetation cover due to water stress caused by evapotranspiration. On the other hand, the residual analysis results (r = − 0.55, z-stat = − 11.58, p < 0.01) indicated a strong relationship between vegetation change and environmental policies implemented within the specified study period. Overall, the study revealed that environmental policies had a greater impact than climate variables on vegetation. Policymakers should, therefore, prioritize implementing effective environmental policies to restore degraded ecosystems and mitigate the effects of climate change.